MAGNETIC CHARACTERISTICS AND MINERAL COMPOSITION ANALYSIS OF KARST ROCKS FROM RAMMANG-RAMMANG KARST AREA, MAROS REGENCY, SOUTH SULAWESI, INDONESIA - Risda Syahruni; Agus Susanto; Muhammad Arsyad; Subaer Subaer; Husain Husain (Indonesian Physical Review, 2026)
This study investigates the magnetic characteristics and mineral composition of rocks in the Rammang-Rammang Karst area, Maros Regency, South Sulawesi, Indonesia, to clarify lithological variability and its implications for local magnetic anomalies. A total of 25 rock samples collected from field sampling points were analysed using a Bartington Susceptibility Meter, while five samples were further examined with a Vibrating Sample Magnetometer (VSM), X-Ray Fluorescence (XRF), and X-Ray Diffraction (XRD). The magnetic susceptibility values range from –0.6 to 10.5 m³/kg, indicating a predominance of diamagnetic behaviour with minor contributions from paramagnetic and antiferromagnetic minerals. Hysteresis curve analysis from VSM confirmed the consistency between magnetic responses and susceptibility measurements. XRF results show that Ca dominates the rocks (>95%), with minor amounts of Fe, Ti, Si, Mn, Cu, Sr, Mo, In, and Co, as well as trace amounts of rare-earth elements (Lu, Eu). XRD analysis confirmed calcite (CaCO₃) as the principal mineral phase, with crystallite sizes ranging from 39 to 44 nm, and the presence of dolomite in sample T18. The spatial distribution of magnetic susceptibility indicates that most of the study area exhibits low and negative values, reflecting diamagnetic behaviour. Whereas the highest value occurs at sampling point T12, which localizes the highest-susceptibility area, marked in red. These results indicate that the magnetic variability of Rammang-Rammang rocks is controlled by minor accessory magnetic minerals, providing valuable insights for mineral exploration and mitigating local magnetic anomalies.